Treatment of Acute Psychosis with Second-Generation Antipsychotics in a Patient with Left Temporal Lobe Lesion - Richard Shehane; Steve Miller; Luke Suber; Miranda Chakos (Case Reports in Psychiatry)
We present a case of rapid onset severe psychosis followed by suicide attempt in a United States Navy sailor. Investigation revealed a left temporal lobe brain mass suspicious for low-grade glioma. After hospitalization and medical management with olanzapine and lurasidone the patient’s psychosis improved. The purpose of this paper is to add to the existing case reports that suggest a relationship between temporal lobe lesions and psychiatric illness, specifically psychosis. In addition, this case adds insight into the effectiveness of medical therapy for brain tumor patients that are not immediate candidates for neurosurgical intervention.